THERAPEUTIC POTENTIAL OF MODERN PROBIOTICS - N. I. Ursova (Педиатрическая фармакология, 2013)
This discussion article adduces a short review of clinical studies where the use of probiotics has shown the best results. The issues of whether probiotics are capable of having a protective effect on the intestinal barrier, an antagonist effect – on opportunistic microbes and a stimulatory effect – on the immune system, are discussed. The best studied production species and strains forming probiotic drugs are observed. The differences between monostrain and multispecies probiotics are given. The reasonability of using combined drugs with combinational additive or synergetic strain-specific effects is explained.